Podwójne znaczenie scen homeryckich - Zieliński, Karol (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The double meaning of scenes is an important element in the reconstruction of how the poems were composed. I take the position that if all the elements – speaking as succinctly as possible, the whole magnitude and artistry of Homer’s poems, warrant their relationship with the oral tradition, then their connection with written culture is redundant. The starting point for any analysis of the composition of these works is based on the assumption that the singer/reciter in the oral tradition shapes his song/recitation so as to command and retain the interest of his audience.
Keywords: Homer; Iliada; Odyseja; poezja epicka; tradycja oralna